Fluorescent Sensory Microparticles that "Light‐up" Consisting of a Silica Core and a Molecularly Imprinted Polymer (MIP) Shell1. Issue 27 (28th May 2013) - Wan, Wei; Biyikal, Mustafa; Wagner, Ricarda; Sellergren, Börje; Rurack, Knut
<x xml:space="preserve">Abstract</x> From darkness came light: Incorporation of urea‐based fluorescent dyes in an anion‐imprinted thin polymer shell coated onto silica microparticles leads to a unique and highly enantioselective fluorescent "light‐up" response to analytes (see scheme, MIP molecularly imprinted polymer).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>